Semiotics of Factory Printed Wax Prints across West Africa - Sawyerr, Naa Omai; Acquaye, Richard; Kusi, Cynthia Agyeiwaa (International Journal of Culture and Art Studies, 2023)
This research explores the topic of factory-printed wax fabrics in West Africa, focusing on their portrayal and significance within the region. The study examines the resemblances and distinctions of these prints across different countries, as well as their applications, meanings, and interpretations. The historical and cultural importance of wax prints in West African society, culture, and economy is emphasized, highlighting the diverse meanings embedded within seemingly uniform designs. The research methodology involves qualitative research and selective sampling, with ten wax print designs chosen for analysis in Ghana, Nigeria, Cote d'Ivoire, and Togo. These countries were selected based on their integration, trade, production, and cultural significance related to wax prints. Data collection involved meticulous observation, thorough documentation, interviews, and thematic analysis. The findings reveal both similarities and differences among the analyzed designs, each representing unique narratives and embodying cultural significance. These prints are not just patterns, but also vessels of history, with captivating stories intertwined with their origins. To ensure the preservation and relevance of these visual representations for future generations, it is recommended to undertake comprehensive documentation and cataloging of traditional wax prints.